Linking Children$1 (Bs Learning With Professional Learnings Impact, Evidence and Inclusive Practice - Keay, Jeanne K.; Lloyd, Christine M.; SpringerLink (Online service) (Rotterdam : SensePublishers, 2011)
Producing evidence that professional development undertaken has an impact on children$1 (Bs learning is an increasingly important issue in education. This book proposes a process model designed to support and enable education professionals to focus on this issue as an integral part of their daily work. This model centres around the identification of professional learning needs in relation to the learning needs of children and focuses on evidence of impact as part of that process. For this model to work effectively, however, there must be a culture which supports, enables and recognises the value and importance of professional learning and development and which is inclusive and child centred. This culture, its elements and its development are also addressed and provide the context and underpinning for the model. In the second part of the book research undertaken to develop and pilot the model with a range of education professionals is discussed and the model is further developed to support education practitioners, leaders and professional development providers to ask questions that are specific to their roles and responsibilities. This book will be of interest to a range of professionals teaching, leading, working, studying and researching in compulsory and post-compulsory education. It also has relevance for the increasing number of providers of learning and development opportunities for education professionals.s
Keywords: Education; Education; Professional & Vocational Education; Electronic books